2018
DOI: 10.1016/j.jid.2018.03.471
|View full text |Cite
|
Sign up to set email alerts
|

464 Analysis of IL36RN and CARD14 gene mutation in Japanese patients with generalized pustular psoriasis and palmoplanter pustulosis

Abstract: IL36RN mutations and CARD14 mutations are reportedly responsible for generalized pustular psoriasis (GPP), palmoplanter pustulosis (PPP) and other pustular diseases. IL36 receptor antagonist deficiency, or DITRA, is thought to stem from the IL36RN gene mutation in GPP. In this study, we discuss a patients background, disease characteristics, and IL36RN and CARD14 gene mutations in patients with GPP and PPP who visited our department after 2013. We assessed the severity of skin lesions using the Psoriasis Area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As such, blockade of the IL-36 pathway could be an effective therapeutic approach for GPP. 1,5,18,[33][34][35][36][37][38] In the Effisayil™ 1 study (NCT03782792), patients with a GPP flare treated with spesolimab, a humanized anti-IL-36 receptor monoclonal antibody and the first targeted treatment for GPP to be studied in a randomized clinical trial, achieved rapid pustular and skin clearance with an acceptable safety profile. 39 At Week 1, the primary endpoint (Generalized Pustular Psoriasis Physician Global Assessment [GPPGA] pustulation subscore of 0, no visible pustules) was achieved by 54% of patients receiving spesolimab compared with 6% receiving placebo (one-sided p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, blockade of the IL-36 pathway could be an effective therapeutic approach for GPP. 1,5,18,[33][34][35][36][37][38] In the Effisayil™ 1 study (NCT03782792), patients with a GPP flare treated with spesolimab, a humanized anti-IL-36 receptor monoclonal antibody and the first targeted treatment for GPP to be studied in a randomized clinical trial, achieved rapid pustular and skin clearance with an acceptable safety profile. 39 At Week 1, the primary endpoint (Generalized Pustular Psoriasis Physician Global Assessment [GPPGA] pustulation subscore of 0, no visible pustules) was achieved by 54% of patients receiving spesolimab compared with 6% receiving placebo (one-sided p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the interleukin (IL)‐36 pathway plays a key role in the pathology of GPP, and several studies have indicated that Asian patients with GPP have high rates (46.8%–81.8%) of mutations in IL36RN , the gene encoding the IL‐36 receptor antagonist. As such, blockade of the IL‐36 pathway could be an effective therapeutic approach for GPP 1,5,18,33–38 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation